Pengembangan Komik Digital Berbasis Cerita Parabel Untuk Meningkatkan Pemahaman Konsep Jenis Segitiga Berbantuan Teorema Phytagoras - Anisa Septyarini; Dyana Wijayanti; Mohamad Aminudin (RANGE: Jurnal Pendidikan Matematika, 2023)
The main objective of this research was to develop a digital comic based on a valid and effective parable story that can improve understanding of the concept of triangle types with the help of the Pythagorean theorem. The method used was research and development using the Borg and Gall development model. The subjects of this study were students of class VIII A MTs NU 01 Pecalungan Batang, totaling 30 students. Collecting data was done through expert validation questionnaires, product-related responses, and students' concept understanding tests. The results of this research and development were that learning media in the form of Digital Comics Based on Parable Stories were declared valid based on the validation results of material experts and media experts, as well as teacher and student response questionnaires. This study also showed an increase in students' pretest scores and post-test scores, so the media was also effective in increasing students' understanding of concepts. With this research and development, it is hoped that it can be used as an interest to develop other innovations that are effectively used in learning.